KONTRIBUSI KETERAMPILAN MEMBACA PEMAHAMAN TEKS CERITA FANTASI TERHADAP KETERAMPILAN MENULIS TEKS CERITA FANTASI SISWA KELAS VII SMP PEMBANGUNAN LABORATORIUM UNP - Nurhafika, Nurhafika; Hafrison, Mohd. (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACTÂ The purpose of this research there are three. First, it describes the skills of reading comprehension text story fantasy grade VII SMP Pembangunan Laboratorium UNP. Second, describing a fantasy story text writing skills grade VII SMP Pembangunan Laboratorium UNP. Third, describe the contribution of the reading comprehension skills of fantasy with story text write text stories fantasy grade VII SMP Pembangunan Laboratorium UNP. This research type is quantitative descriptive method. The design used in this research is the design contribution. This research population is grade VII SMP Pembangunan Laboratorium UNP are registered on the 2018/2019 school year, that is, 85 students. The sample in this research is determined using the purposive sampling of the population, i.e., 59 students. Research data is a score test results intermediate reading comprehension text story fantasy and score the writing skills test result text story fantasy. Research instrument is an objective test to measure the skills of reading comprehension text story fantasy and performance tests to measure the writing skills text story fantasy. The results of the research there are three. First, the skills of writing fantasy stories text grade VII SMP Pembangunan Laboratorium UNP are on more than enough qualifications (LdC). Second, the skills of reading comprehension text story fantasy grade VII SMP Pembangunan Laboratorium UNP are on more than enough qualifications (LdC). Third, intermediate reading comprehension text story fantasy contributions amounting to 21.25% against writing skills text story fantasy grade VII SMP Pembangunan Laboratorium UNP.Â Kata kunci: Kontribusi, Keterampilan, Membaca Pemahaman, Menulis, Teks Cerita Fantasi